Disability and Care in Late Medieval Lund, Sweden: An Analysis of Trauma and Intersecting Identities, Aided by Photogrammetric Digitization and Visualization - Nolan Blair; Fritz Sandra Tornberg; Derudas Paola; Dininno Domenica; Tornberg Anna (Open Archaeology)
This article is a Bioarchaeology of Care and Disability focused analysis of an individual who suffered a severe fracture of the left knee in Late Medieval Lund, Scania (1300–1536 CE). We question the degree to which written sources from the period represent the reality of the disability experience, and to that end how identities intersect in the Medieval urban landscape. Following an index of care model methodology, we provide an interpretation of the pathological evidence within the archaeological and historical context of Medieval Lund. In this case, the individual received both short and long-term care, which included treatment of pain and inflammation, assistance with hygiene and nutrition, and the management of disability as a result of physical impairment for the remainder of the individual’s life. Their treatment in death with a prominent burial position close to the church, a symbol of upper social status during the Medieval period, demonstrates that the identity of disability in the past is a much more complex process than can be gleaned from the written sources. Our analysis also employed 3D online visualization and annotation solutions to aid in the analysis and dissemination of our results, making data more accessible to readers and researchers alike.